53 Injuries among university students – self-harm and drunk driving. (1st September 2016) - Honkala, Emma; Funk, Tjede; Partonen, Timo; Parkkari, Inkeri
Abstract : Deliberate self-harm has received considerable attention during the last years. Researchers consider it to be a coping strategy used to manage emotional distress and release tension. University students often encounter these feelings. Studies also suggest that self-harm might be more common than previously expected, one study indicating that 14% of the sample of 500 university students had engaged in self-harm at least once during their lifetime. In addition to self-harm, alcohol impaired driving is also common among university students, and maybe unsurprisingly, driving under the influence of alcohol is one of the main causes of road traffic accidents among young drivers. Such risky and self-destructive behaviours deserve attention. The aim of this workshop is to give more insights into the types of injuries young adults and university students in particular are likely to encounter. Two keynote speakers will provide the background for this workshop. Timo Partonen, adjunct professor of Psychiatry at the University of Helsinki and a research professor at National Institute for Health and Welfare, will talk about the ways in which direct and indirect self-harm can be detected and what are the most common risk factors behind these incidents. He will also give suggestions on how to deal with such cases and where to find help. The second speaker, M.Sc. (Psychology) Inkeri Parkkari, Chief Adviser at Finnish Transport Safety Agency, is going to discuss the types of risk factors that contribute to traffic accidents among young people by giving examples of different case studies. She will also address young people's perceptions of the most effective interventions to reduce these casualties. The workshop will provide several opportunities for participants to interact with speakers and with each other.